Ecological Sovereignty from an Islamic Perspective: Surpassing National Sovereignty and Legal Responsibilities - Azwir Abdul Azis, Fouza; Sukaraja, Detania (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-Undangan dan Ekonomi Islam, 2024)
Ideally, countries are responsible for protecting the environment sustainably through international cooperation. Islamic law offers principles such as khilafah (human stewardship of the earth), amanah (responsibility), and mizan (balance) to guide humanity in preserving nature. However, in reality, state sovereignty often hinders addressing cross-border environmental issues, with many countries prioritizing national interests. The implementation of Islamic environmental law is also suboptimal and underappreciated in international legal discourse. This study employs qualitative methods, including literature analysis and comparative approaches, to explore Islamic legal principles through sources like the Qur'an, Hadith, and fatwas. It compares Islamic legal approaches with international legal frameworks to identify potential integrations that can enhance global environmental preservation efforts. The findings indicate that Islamic law offers a unique perspective that enriches the global discourse on ecological sovereignty. Integrating Islamic legal principles into international legal frameworks can create more sustainable and equitable approaches, strengthening global efforts in environmental preservation and contributing to sustainable development for all beings on earth.